Prediction of bronchopulmonary dysplasia course in children by analyzing clinico-biochemical indicators - L. M. Chernenko (Zaporožskij Medicinskij Žurnal)
At the present stage, one of the most important issues of pediatric pulmonology is to find ways of preventing the progression of chronic lung diseases. The concept of the natural course of disease has emerged among some pathological conditions, that is, the course of disease from the onset to symptoms resolution or control, which is understood as programs designed to reduce the incidence or prevalence or eliminate these diseases. In this regard, bronchopulmonary dysplasia is no exception and represents a chronic polyetiological disease associated with arrested lung development.